Fever in the returning child traveller: approach to diagnosis and management. Issue 10 (25th March 2014) - Halbert, J; Shingadia, D; Zuckerman, Jane N
Abstract : During the last half century there has been an exponential increase in international travel including to more exotic and long-haul destinations. The assessment of febrile returning child travellers presents diagnostic challenges and is often performed poorly. A detailed travel and medical history, clinical examination and appropriate first-line investigations are essential. While the majority of children will have a common self-limiting or easily treatable infection, it is important to consider other causes, including imported infections, which may be life-threatening or highly contagious. In this article, we provide guidance on the initial assessment and management of such children with a focus on some of the more important imported infections, including malaria, dengue, typhoid fever, travellers' diarrhoea, respiratory infections, tuberculosis, schistosomiasis and rickettsial diseases.